Self-reported prevalence, pain intensity and risk factors of low back pain in adolescent rowers - Ng, Leo; Perich, D.; Burnett, A.; Campbell, Amity; O'Sullivan, Peter (Elsevier Australia, 2013)
Objectives: The primary objective of this study was to determine the lifetime and point prevalence of low back pain, the related pain intensity and the rowing-related aggravating factors for low back pain in adolescent rowers who participated in school-level competitions. The secondary objective was to determine whether between-gender differences existed in these data. Design: Retrospective cross-sectional survey. Method: 130 adolescent male and 235 adolescent female rowers aged between 14 and 16 years were recruited in this study. Participants completed a questionnaire to determine their lifetime and point prevalence of low back pain, their pain intensity and rowing-related factors that aggravated their low back pain. Results: A high lifetime and point prevalence of low back pain were found in both adolescent male (93.8% and 64.6%, respectively) and female (77.9% and 52.8%, respectively) rowers. A significant between-gender difference was reported for both statistics (p < 0.001). A significantly lower (p = 0.003) level of pain intensity via a visual analog scale was found for males (4.1/10) when compared to females (5.0/10). Similar rowing-related aggravating factors were reported by males and females although fewer males reported that lifting the rowing shell aggravated their low back pain. Conclusions: A high lifetime and point prevalence of low back pain was reported by the adolescent rowers recruited in this study. While a greater proportion of adolescent male rowers reported low back pain, they reported a lower intensity of pain when compared to their female counterparts. Coaches, clinicians and rowers should be made aware of these findings such that future research and development can focus on promoting pain management strategies in this sport.